Myopathy in patients with HashimotoÂ´s Disease. - Villar, Jaqueline; Finol, Héctor; Torres, Sonia; Roschman, Antonio (Investigación Clínica, 2015)
Hashimoto thyroiditis (HT) is an autoimmune disease of the thyroid gland. Patients may present or not a hypothyroid state, and frequently have manifestations of myopathy. The present work was aimed to assess the clinical symptoms and signs of skeletal muscle alterations in HT, describe the muscular pathological changes and relate them to the functional thyroid status and to the autoimmune condition of the patient. Clinical and laboratory studies were performed in ten HT patients and three control subjects (hormonal levels and electromyography). Biopsies from their vastus lateralis of quadriceps femoris muscle were analyzed under light (histochemistry and immunofluorescense) and electron microscopy. All patients showed muscle focal alterations, ranging from moderate to severe atrophy, necrosis, activation of satellite cells, presence of autophagosomes, capillary alterations and macrophage and mast cell infiltration, common to autoimmune diseases. The intensity of clinical signs and symptoms was not related to the morphological muscle findings, the electromyography results, or to the state of the thyroid function. Reactions for immunoglobulin in muscle fibers were positive in 80% of the patients. Fiber type II proportion was increased in all patients, with the exception of those treated with L-thyroxine. In conclusion, autoimmune processes in several of the patients may be associated to the skeletal muscle al terations, independently of the functional state of the thyroid gland; however, fiber II type proportion could have been normalized by L-thyroxine treatment.